2010
DOI: 10.1111/j.1349-7006.2009.01457.x
|View full text |Cite
|
Sign up to set email alerts
|

High expression of BUBR1 is one of the factors for inducing DNA aneuploidy and progression in gastric cancer

Abstract: Gastric cancers show high frequency of DNA aneuploidy, a phenotype of chromosomal instability. It is suggested that the abnormal spindle assembly checkpoint is involved in DNA aneuploidy, but the underlying mechanism is still unclear. We studied the mechanism by assessing the expression of BUBR1 in gastric cancer. The DNA ploidy patterns of 116 gastric cancer samples obtained from the Department of Surgery and Science at Kyushu University Hospital were analyzed. Of those, DNA aneuploidy was seen in 70 (60.3%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 38 publications
1
51
1
4
Order By: Relevance
“…All three of these kinases have recently been shown to have a role in other malignancies and are interesting candidates for genes in the context of the malignant transformation of plexiform neurofibromas: BUB1B and BUB1 are part of the spindle assembly checkpoint that ensures proper segregation of the chromosomes. [36][37][38][39] Alterations in BUB1B have been documented in a number of cancers including breast cancer, lung cancer, colon cancer and gastric cancer. 37,38,[40][41][42][43][44] In these, BUB1B overexpression appears associated with more aggressive behavior, increased proliferative activity, genomic complexity, chromosomal instability and DNA aneuploidy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All three of these kinases have recently been shown to have a role in other malignancies and are interesting candidates for genes in the context of the malignant transformation of plexiform neurofibromas: BUB1B and BUB1 are part of the spindle assembly checkpoint that ensures proper segregation of the chromosomes. [36][37][38][39] Alterations in BUB1B have been documented in a number of cancers including breast cancer, lung cancer, colon cancer and gastric cancer. 37,38,[40][41][42][43][44] In these, BUB1B overexpression appears associated with more aggressive behavior, increased proliferative activity, genomic complexity, chromosomal instability and DNA aneuploidy.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39] Alterations in BUB1B have been documented in a number of cancers including breast cancer, lung cancer, colon cancer and gastric cancer. 37,38,[40][41][42][43][44] In these, BUB1B overexpression appears associated with more aggressive behavior, increased proliferative activity, genomic complexity, chromosomal instability and DNA aneuploidy. 37,[40][41][42][43]45,46 Interestingly, aneuploidy and complex karyotype are common finding in malignant peripheral nerve sheath tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the dysregulated genes identified in 5 and more studies, such as MAD2L1 GJA1 ( BUB1B, a member of the BUB (budding uninhibited by benzimidazole) gene family, is one of the key molecules in the spindle assembly checkpoint. High expression of BUB1B has often been reported in several malignancies and correlated with chromosomal instability (43,44). In this study, our results showed for the first time that BUB1B protein was upregulated in NPC compared with chronic inflammation of nasopharyngeal mucosa and normal adjacent epithelia of NPC, and that the high expression of BUB1B was associated with the prognosis of NPC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Microsatellite analysis was performed using fluorescent-labeled primers and an automated DNA sequencer as previously described [16,17,20,22]. Briefly, genomic DNA isolated from cancerous and corresponding noncancerous tissue specimens was used to amplify microsatellite loci by PCR using primer sets labeled with the fluorescent compounds, 6-carboxy-X-rhodamine or 6-carboxy-20,40,70,4,7,-hexachloro-fluorescein.…”
Section: Methodsmentioning
confidence: 99%
“…CCAT2 expression was evaluated using the Fast SYBR Green Master Mix PCR Kit (Life Technologies), and transcript levels were normalized to those of β-actin as an endogenous control. The oligodeoxynucleotide primers were as follows: CCAT2 , 5′-CCCTGGTCAAATTGCTTAACCT-3′ (forward) and 5′-TTATTCGT- CCCTTTTTATGGAT-3′ (reverse) and β-actin, 5′-CCACGAAACTACCTTCAAC-3′ (forward) and 5′-GATCTTCATTGTGCTGGG-3′ (reverse) [20,21]. …”
Section: Methodsmentioning
confidence: 99%